Investigating the role of illustrations/visual elements on adult reading habits and literary attraction - Vaze, Amrita Mayuresh; Pawar, Ganesh; Rajwade, Pallavi (BBDS - Black Book: Drawing and Sketching, 2024)
Illustration is a thing that it can show things that a pictures are not able to show . Illustration can be considered as visual representation of the text . Illustration may have positive as well as negative effects on the reader like it makes easy for the reader to understand the concept easily and sometimes the presence of illustration can be disturbing to some people . The research aims to look for the role which illustration plays in adult’s literature and reading habits and their literary attraction . The method used is a survey method. Survey was conducted by circulating a google form .The sample population is from the age group 18 to 65 from Pune city. Most of the participants preferred books with illustrations and with specific illustration styles. Participants also agreed that illustration play a crucial role in influencing the readers literary attraction.